2015
DOI: 10.1128/jvi.02022-14
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 and Morphine Regulation of Autophagy in Microglia: Limited Interactions in the Context of HIV-1 Infection and Opioid Abuse

Abstract: About 50% of individuals infected with HIV-1 will develop some sort of neurocognitive impairment that cannot be prevented nor eradicated by antiretroviral therapy. The neuropathogenesis is mostly due to inflammatory responses by infected microglia, the resident immune cells of the brain. Cognitive disorders may also be associated with drugs of abuse. In fact, opioid drug users have an increased risk of developing neurocognitive disorders with increased progression to dementia. Although the mechanism(s) by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
93
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 73 publications
12
93
0
Order By: Relevance
“…[40][41][42][43] In addition to the known etiological agents, drugs of abuse such as cocaine, morphine and amphetamines, are also known to induce ER stress and autophagy in various cell types of the CNS, thereby exacerbating the disease pathology. 14,34,44 Several reports have implicated a central role for ER stress in the induction of autophagy in the pathogenesis of various neurodegenerative diseases mediated by diverse stressors. [45][46][47][48][49][50] In the current study, we demonstrate for the first time a molecular link between ER stress-mediated activation of autophagy and the induction of astrogliosis that is accompanied with the release of proinflammatory cytokines in cocainetreated human astrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] In addition to the known etiological agents, drugs of abuse such as cocaine, morphine and amphetamines, are also known to induce ER stress and autophagy in various cell types of the CNS, thereby exacerbating the disease pathology. 14,34,44 Several reports have implicated a central role for ER stress in the induction of autophagy in the pathogenesis of various neurodegenerative diseases mediated by diverse stressors. [45][46][47][48][49][50] In the current study, we demonstrate for the first time a molecular link between ER stress-mediated activation of autophagy and the induction of astrogliosis that is accompanied with the release of proinflammatory cytokines in cocainetreated human astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…28 The cellular and molecular mechanism(s) leading to astrogliosis mediated by diverse agents as well as the related neuroinflammatory pathways that trigger astrogliosis are still areas of active investigation. While the role of drugs of abuse, such as morphine and methamphetamine, on induction of apoptosis, HIV disease progression, neuronal injury and neurodegeneration has been well established, [34][35][36][37][38][39] information in how the drugs influences astrogliosis and the role of autophagy in this process is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, El-Hage et al previously have demonstrated decrease in autophagy on combined morphine-Tat treatment in human microglia. 51 Although Dever et al 52 also report lower autophagy activity in neurons on MCT coexposure initially at 8 h post-treatment, increased autophagy was observed at 24 h of combined treatment, again establishing cell-type-dependent differences in the autophagy response.…”
Section: Discussionmentioning
confidence: 98%
“…However, role of autophagy in cocaine-mediated deleterious effect in the brain remains poorly understood. Several recent studies with other psychostimulants suggest involvement of autophagy in neurotoxicity [30,33]. For example, morphine-mediated autophagy is responsible for the development of morphine antinociceptive tolerance [39] and methamphetamine has been reported to induce cell death via autophagy [40].…”
Section: Discussionmentioning
confidence: 99%